Stimuli responsive aggregation-induced emission of bis(4-((9H-fluoren-9-ylidene)methyl)phenyl)thiophene single crystals. (3rd June 2019) - Kazantsev, Maxim S.; Sonina, Alina A.; Koskin, Igor P.; Sherin, Peter S.; Rybalova, Tatyana V.; Benassi, Enrico; Mostovich, Evgeny A.
Abstract : BFMPT crystals demonstrate stimuli-responsive and conformation-dependent aggregation-induced emission. Abstract : Aggregation induced emission (AIE) materials are in the spotlight of current materials development due to their unique properties and potential applications in light-emitting devices, bio-imaging and sensors. In this work we synthesised and thoroughly studied a novel luminogen based on bis(4-((9 H -fluoren-9-ylidene)methyl)phenyl)thiophene (BFMPT) showing polymorph-dependent AIE. BFMPT crystallises in two polymorphs of different crystal shapes and colours, however both of them are highly-luminescent with the same photoluminescence (PL) quantum yield of 40%. Polymorph I can undergo irreversible phase transition to polymorph II. Deep quantum chemical study of BFMPT revealed that inter- and intramolecular interactions in both polymorphs are very similar and the main contributor to the optical difference between the polymorphs is a variation of BFMPT conformation. The thermal stress was demonstrated to negligibly affect the PL efficiency of BFMPT crystals. Due to high intrinsic torsional freedom and high solid-state PL efficiency, BFMPT could serve as a basis for the molecular design of high performance AIE materials.